Digital Marketing for Improving Brand Image at Al-Munawwir Komplek Q Islamic Boarding School in Yogyakarta - Chotimah, Chusnul; Akrom, Nur Kholifah (Jurnal Tarbiyatuna, 2024)
This research aims to study the implementation of digital marketing to improve brand image of Al Munawwir Komplek Q Boarding School in Yogyakarta. Using qualitative approach, this research involves participative observation, in-depth interview, and documentation. The main informants are the head of the boarding school and the coordinator of media and publication division. The research results show that Komplek Q uses six digital platforms for marketing: website, Facebook, Instagram, Twitter, Youtube, and TikTok. These platforms significantly increase the number of new students by regularly publishing the activities of the boarding school in interesting ways. The advantages of digital marketing at Komplek Q include superior programs, collaboration with alumni, and collaboration with other Islamic boarding schools. The power of digital marketing at Komplek Q is that it is fully supported by the boarding school’s leaders, and it involves the whole management in all levels and the students. The uniqueness of digital marketing is in the ability of the Islamic boarding school to attract the interest of various age groups and form formal educational institutions under the auspices of the boarding school. The research concludes that effective digital marketing can significantly improve the brand image of the Islamic boarding school through well-planned and collaborative strategies.